RE-DESIGN MESIN FERMENTASI ROTI MENGGUNAKAN PENDEKATAN VALUE ENGINEERING (VE) - Hidayat, Rachmad; Arenda, Anis (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
The purpose of this study is to improve engine performance by improving the fermentation of bread heat distribution patterns in the machine and increase energy use efficiency by reducing energy consumption of electricity grid using alternatives other energy sources. In this study, the calculation method used three expert assessments of each alternative posed by using the fishbone diagram to diagnose the existing problems in fermentation machine. Histogram which determined the amount of costs required by each alternative is rosen based on factual data and by using Analytic Hierarchy Process (AHP) to determine the criteria and weighting of each alternative based on the assessment of the three experts. The results showed that the value and performance of the alternative energy source is more competitive compared to other alternatives. The best alternative bread fermentation machine is one with an alternative energy source without the use of automated pipeline gas systems.